2022
DOI: 10.3389/fmars.2022.847600
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Phylogeny of Two Tintinnid Ciliates of Leprotintinnus (Protista, Ciliophora, Choreotrichida) Combining the Loricae, Cytological, Ontogenetic Features, and Barcoding Genes

Abstract: Tintinnid ciliates are a highly diverse and essential group in the marine planktonic microbial loop. However, most of the known tintinnids were recorded only by the lorica characters and very few of them had been studied on their cytological features. In this study, the morphological characters of the lorica, ciliary pattern, nuclear apparatus, ontogenesis, and the molecular phylogeny of two poorly known tintinnid ciliates, Leprotintinnus nordqvisti (Brandt, 1906) Kofoid and Campbell (1929) and L. simplexSchmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However, some species may show polymorphism in lorica, a phenomenon that cannot be ignored in both the Arctic and Antarctic zones (Dolan et al 2012). Recently, culture experiments on individuals of Helicostomella species and DNA experiments on individuals of Leprotintinnus nordqvisti have confirmed the polymorphism of tintinnid species (Santoferrara et al 2015;Hu et al 2022). Genetic studies (e.g., Kim et al 2013) have confirmed the existence of polymorphism, but the distribution of different morphs is still not properly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, some species may show polymorphism in lorica, a phenomenon that cannot be ignored in both the Arctic and Antarctic zones (Dolan et al 2012). Recently, culture experiments on individuals of Helicostomella species and DNA experiments on individuals of Leprotintinnus nordqvisti have confirmed the polymorphism of tintinnid species (Santoferrara et al 2015;Hu et al 2022). Genetic studies (e.g., Kim et al 2013) have confirmed the existence of polymorphism, but the distribution of different morphs is still not properly understood.…”
Section: Introductionmentioning
confidence: 99%